2006
DOI: 10.1111/j.1365-2265.2006.02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic features of the X chromosome affect pubertal development and testicular degeneration in adolescent boys with Klinefelter syndrome

Abstract: Paternal origin of the supernumerary X chromosome is associated with later onset of puberty and longer CAG repeats of the AR with later pubertal reactivation of the pituitary-testicular axis in KS boys. Identifying genetic factors that affect the phenotype may lead to a better understanding of the pathogenesis of KS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…In another study, however, the only parameter associated with CAG repeat length was penile length; the correlation was inverse [63]. In addition, KS boys with a longer CAG repeat show later onset and slower progression of puberty and slower testicular degeneration process [60]. These findings are in agreement with diminished AR response to androgens when the AR gene has a longer CAG repeat.…”
Section: Genetic Mechanisms Of Gonadal Failuresupporting
confidence: 77%
See 2 more Smart Citations
“…In another study, however, the only parameter associated with CAG repeat length was penile length; the correlation was inverse [63]. In addition, KS boys with a longer CAG repeat show later onset and slower progression of puberty and slower testicular degeneration process [60]. These findings are in agreement with diminished AR response to androgens when the AR gene has a longer CAG repeat.…”
Section: Genetic Mechanisms Of Gonadal Failuresupporting
confidence: 77%
“…The supernumerary X chromosome is paternal in 40–60% and maternal in 40–60% of KS cases [3, 7, 59]. In our study of 14 adolescent KS boys, the 3 subjects with an additional paternal X chromosome showed later onset and slower progression of puberty [60]. Other studies [61,62,63] have, however, suggested that parental origin of the extra X chromosome has no evident effect on the phenotypes of KS males.…”
Section: Genetic Mechanisms Of Gonadal Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple genetic mechanisms may explain this phenotypic variability, all related to the presence of a supernumerary X chromosome. The excessive dosage of X-linked genes that escape inactivation, skewed X-inactivation, and the parental origin of the supernumerary X chromosome may all influence the phenotypical characteristics of men with KS (23)(24)(25)(26). Because 10% of protein-encoding genes on the X chromosome are testis-specific, it is not surprising that testicular function is affected in men with KS (5).…”
Section: Discussionmentioning
confidence: 95%
“…Inactivation of the excessive X chromosome(s) occurs in men with KS, but increased expression of genes located on the X chromosome that escape inactivation might play an important role. It is assumed that 15% of X-linked genes escape inactivation (26). It is, however, not clear whether the abnormal karyotype affects the germ cells or rather the somatic niche cells.…”
Section: Discussionmentioning
confidence: 99%